Black-box modeling and adaptive control of hybrid thermoelectric refrigerator systems
Vaccines carrier has been used to keep the temperature within 2–8°C. However, a poorly functioning vaccines carrier may expose the vaccines to freezing temperatures. Hybrid Thermoelectric Refrigerator (H-TER) systems are developed in order to transport sensitive vaccines to hospitals at accurate controlled temperature. The refrigerator use air-to-air and direct thermoelectric heat pumps. This work reports on modeling and control studies carried out for H-TER systems that can control low temperature accurately. Different type of material containers (aluminium and stainless steel) is used and comparisons between them are analyzed. The systems are nonlinear and exhibits varying model parameters and dead-time. The objective of the study is to investigate control strategies that are based on non-priori plant knowledge and yet allowing for continuous adaptations of the controller to changing system dynamics. In fact, the various cooling load also causes a reduction of refrigerator efficiency including the fluctuation of imposed current level due to electronic component performance and varied operating condition of thermoelectric module on cold and hot ends against time. Thus an adaptive control system is considered to handle the problems that are stipulated above. A black box modeling approach is chosen since this is needed for the implementation of adaptive controllers. The H-TER systems have been identified using both Recursive Least Squares (RLS) and Recursive Extended Least Squares (RELS) methods. Since RELS has shown to give biased estimates for filtered data and slow convergence estimates for unfiltered data, RLS has been chosen for the model as its give a better representation of the systems. A second order model of H-TER I and HTER II systems are found to adequately represent the system as it give best fit of 0.0009 and 0.0007 respectively which made the fourth order to be insignificant for implementation. Validation procedures using second order model for online estimation, show that the model is indeed a good representation of the H-TER systems. On-Off and PI controllers are the commonly used in thermoelectric system is applied to this system as case studies. PI controller shows better performance over On-Off controller in term of steady state error.